O aspecto verbal em Apolodoro: um estudo baseado em corpus sobre os padrões de usos aspectuais em Biblioteca - Trindade, Alexandre Wesley [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The aim of this work was to analize the patterns of aspect usages in Greek writer Apollodorus, by means of empirical approach, from a electronic database and statistically tested. The main methodological underpinning for the exploratory research was provided by Corpus Linguistics because in the fundamental concept language is a probabilistic system and it must be studied by an empirical approach. The assumption of this view of language is that the theoretical possibilities of linguistic features do not correspond with the frequency of occurrence. This difference is not significant only in statistical point of view, it demonstrates that is typical of language the presence of (i) a regular pattern showed and (ii) a systematic variations. As language patterns were considered collocational patterns. The corpus chose was the work Library (Biblioteca in portuguese), whose authorship is attributed to Apollodorus, first century CE. This corpus is therefore suitable for the study of patterns of aspect usages because it is composed of authentic texts in natural language. The identification of verbal aspect was due to the ending location of the pertinent verbal correlate with higher rate of frequency, using the program AntConc, which generated a word list listing the verbs accounted for. From the occurrences of verbs chosen was established the most frequent verbal aspect in order to define the unit of analysis. The selection criterion was given verbal aspects of the opposition of verbal stems, considering the opposition of three verbal stems: present stem, perfect stem, and aorist stem. The corpus used in the AntConc program was not tagged. In order to examine, POS tagging was used to steady in the Perseus Digital Library. Among the sample of verbal occurrences, the stem of the aorist had the highest frequency. Through statistical analysis, collocational pattern infinitive + participle was the most frequent

Este trabalho teve por objetivo analisar os padrões de usos que o autor grego Apolodoro (I d.C.) fez do aspecto verbal, por meio de uma abordagem empírica, a partir de uma base de dados informatizados e estatisticamente verificados. Tratou-se de uma pesquisa exploratória na qual foi utilizada a metodologia fornecida pela Linguística de Corpus, pois no seu conceito fundamental a linguagem é um sistema probabilístico e deve ser estudada por uma abordagem empírica. A pressuposição desta visão da linguagem é a de que as possibilidades teóricas dos traços linguísticos não coincidem com a frequência de ocorrências. Essa diferença é não somente significativa do ponto de vista estatístico, como também ela evidencia que é característico da linguagem a existência de (i) regularidade nos padrões apresentados e (ii) sistematicidade nas variações. Como padrões da linguagem foram considerados os padrões colocacionais. O corpus escolhido foi a obra Biblioteca, cuja autoria é atribuída a Apolodoro, séc. I d.C. Este corpus, portanto, é adequado para o estudo do padrões de usos aspectuais porque é composto de textos autênticos, em língua natural. A identificação do aspecto verbal se deu pela localização da desinência pertinente ao tema verbal correlato, com índice de mais alta frequência, utilizando o programa AntConc, que gerou uma lista de palavras (word list) elencando os verbos contabilizados. A partir das ocorrências de verbos levantadas foi estabelecido o aspecto verbal mais frequente para que se definisse a unidade de análise. O critério de seleção dos aspectos verbais se deu pela oposição de temas verbais, considerando-se a oposição dos três temas verbais: tema do presente, tema do perfeito e tema do aoristo. O corpus utilizado no programa AntConc não estava etiquetado. A fim de proceder à análise foi utilizada a etiquetagem morfossintática constante ...
Keywords: Lingua grega; Linguística; Linguística na literatura; Linguística de corpus; Linguistics in literature